2017
DOI: 10.1016/j.anr.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Moderated Mediation Effect of Self-esteem on the Relationship Between Parenting Stress and Depression According to Employment Status in Married Women: A Longitudinal Study Utilizing Data from Panel Study on Korean Children

Abstract: It is necessary to manage parenting stress among married women through various programs and education that increase self-esteem in order to reduce their level of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Prior studies have shown that mothers, who are more commonly involved in child rearing than are fathers, feel guilty about children's symptoms [16] and exhibit greater parenting stress than do fathers. However, as fathers' role in child rearing is increasing, so too is their parenting stress [17,18]. Further, mothers who are professionals tend to have relatively more parenting stress than do full-time homemakers because they have to balance work and family [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that mothers, who are more commonly involved in child rearing than are fathers, feel guilty about children's symptoms [16] and exhibit greater parenting stress than do fathers. However, as fathers' role in child rearing is increasing, so too is their parenting stress [17,18]. Further, mothers who are professionals tend to have relatively more parenting stress than do full-time homemakers because they have to balance work and family [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, as fathers' role in child rearing is increasing, so too is their parenting stress [17,18]. Further, mothers who are professionals tend to have relatively more parenting stress than do full-time homemakers because they have to balance work and family [18]. Since modern society currently demands equal parenting responsibilities from fathers and mothers, it is necessary to determine the role of parenting stress at the individual level and concerning the couple as a unit [19].…”
Section: Introductionmentioning
confidence: 99%
“…Research on personality development supports the principle of plasticity, which states that the characteristics of self-esteem can be influenced by environmental factors. Stressful events have the potential to cause individual variability in the development of self-esteem because they occur at different moments in life (37)(38)(42)(43) . Thus, stressful events can provide detrimental changes in self-esteem.…”
Section: Depressed Moodmentioning
confidence: 99%
“…Parenting stress affects children's self‐esteem and leads to changes in self‐esteem levels over time (Han & Kim, ). Parents' low self‐esteem leads to dysfunctional relationships with the child, whereas positive self‐esteem can serve as a buffer from negative emotion, thereby promoting parent–child interaction (Porter et al, ).…”
Section: Introductionmentioning
confidence: 99%